2014
DOI: 10.1177/1687814020926788
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic mechanical behavior and constitutive model of polyvinyl chloride elastomers for design processes of soft polymer materials

Abstract: Soft polymer materials are often used in shock absorption, cushioning, and so on. During the design and development process, determining the mechanical behavior and constitutive properties under static and dynamic loads is important to improve product performance. This study aims to analyze the static mechanical performance of polyvinyl chloride elastomers with different Shore hardness levels. Static and dynamic mechanical performance experiments with loading strain rates of 0.1, 1650, 2000, and 2700 s−1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Quasistatic Tensile Experiment. PVC elastomers with three types of Shore hardness (57A, 52A, and 47A) are used as experimental materials in this study [13]. e quasistatic tensile specimen is designed in accordance with SAC GB/T 528-200921 [14] and prepared by die stamping.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quasistatic Tensile Experiment. PVC elastomers with three types of Shore hardness (57A, 52A, and 47A) are used as experimental materials in this study [13]. e quasistatic tensile specimen is designed in accordance with SAC GB/T 528-200921 [14] and prepared by die stamping.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…When direct loading is adopted in the SHTB experiment, the incident wave is a square wave and can reach the maximum strain in a short time, which cannot guarantee constant strain rate loading in the entire loading process. To ensure the accuracy of the SHTB experimental results, a pulse shaper is placed on the end face of the flange (the end face impacted by the sleeve bullet) to obtain the characteristics of the incident wave required (the loading time corresponding to the width of the rising edge of the incident wave is ensured to be greater than the time required for three times of intercourse of the loading pulse in the specimen [13]) and realize constant strain rate loading.…”
Section: Key Technique Of Shtb Experimentmentioning
confidence: 99%
“…Fortunately, some work has been performed on the dynamic mechanical performance of the polymers at high strain rates, which paves the way to explore the mechanical performance of the SMPs under shock loading. Lei et al [ 36 ] found that polyvinyl chloride elastomers exhibit super-elastic and viscoelastic properties under static and dynamic loads, respectively. Fan et al [ 37 ] found that the impact load would cause a significant temperature rise of polyurethane elastomer materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, materials in industrial applications are subjected to not only static but also dynamic loads, probably both at the same time, or both occurring sequentially [ 32 ]. Therefore, it is of great importance to study the combination of the dynamic and static studies of propellants to achieve the inter-conversion of the relaxation modulus and dynamic modulus [ 33 , 34 ], so that dynamic and static experiments or simulations can mutually corroborate. So, how can the numerical conversion of the dynamic storage modulus and relaxation modulus in engineering applications be realized?…”
Section: Introductionmentioning
confidence: 99%